Pengaruh Senam Ergonomis Terhadap Kualitas Tidur Pada Lansia Usia 60-74 Tahun Di BPSTW Ciparay Kab. Bandung 2022 - Reni Rohimah; Rika Susanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
In the elderly sleep disorders during the night decreased slightly occurs around 70-80% effective from adulthood. Pravalensi sleep disorders in the elderly is high at around 67%. Gymnastics Ergonomic dikombinaksikan if the breath with movement and relaxation so as to optimize the oxygen to the brain improves circulation and increases serotonin that can create a sense of calm and sleepy and improve sleep quality. The purpose of this study was to determine the effect on the quality of sleep ergonomic exercise in the elderly aged 60-74 years in Bpstw Ciparay Kab.Bandung 2022. This research uses experimental without pebanding group with pretest and posttest study design one group design. Sample 35 respondents using purposive sampling techniques and Proportionate Stratified Random Sampling. The data collection by questionnaire. Normality test using the Shapiro-Wilk test continued with bivariate analysis using the t test. The results showed changes sigifikan to changes in the quality of sleep before transactions are carried gymnastics 11.94 and after doing gymnastics ergonomically 10.60. Results based on test for normality using the Shapiro-Wilk test the data has a normal distribution ρ = 0.000 (ρ≤0.05) then performed t test obtained by value ρ = 0.000 (ρ≤0.05). This study be concluded that there are significant ergonomic exercise on sleep quality in older adults aged 60-74 years in Bpstw Ciparay Kab.Bandung 2022. Advised on a gymnastic ergonomic researchers do very day to overcome sleep disorders and improve sleep better.